European contract law : Scots and South African perspectives - MacQueen, Hector L.; Zimmermann, Reinhard, 1952 October 10- (Edinburgh studies in law, 2006)
This volume sets out initially to test the claim that, as combinations of Civil and Common Law influences, the mixed systems of contract law in Scotland and South Africa have anticipated the content of the Principles of European Contract Law (PECL) concluded and published in 2003 by the unofficial Commission on European Contract Law. The studies go much further, however. Current official moves towards a European contract law within the European Union lend the critiques of PECL offered in this volume an especial urgency and significance. A European contract law is nearer to reality than ever before, and mere policy critiques of that possibility are no longer enough. Technical and substantive assessments of PECL are also essential. This book provides just such assessments from the perspective of Scots and South African contract lawyers, and is offered to the European debate without prejudice as to the deeper policy questions. At the same time it may help to inform Scots and South African lawyers about the substance of international developments in the field, and suggest ways in which their still vigorous and vital national laws may continue to be developed to remain in step with the needs of the present day.